Phytomodule Cluster as a Structural Element of Indoor Area of Various Functional Purpose - Buyun, L.I.; Ivannikov, R.V.; Yakymets, V.M.; Stepankov, R.S.; Kharytonova, I.P.; Kozhokaru, A.A. (Science and Innovation, 2024)
Introduction. To date, people are surrounded by new toxic substances accompanying the development of technological progress, therefore the searching a new ways for amelioration of indoor air quality has acquired an increasing urgency. Problem Statement. Nowadays, the development of methods for phytoremediation of indoor environment of premises, especially those where congestion of a significant number of people for a long time takes place (treatment and preventive care establishments, classrooms, military barracks or housing accommodations) is increasingly necessary. Purpose. To create cluster of phytoremediation modules to be used for amelioration of indoor air quality. Materials and Methods. The anatomical and morphological, physiological and biochemical, microbiological methods, light and seM microscopy methods were used in the work. Results. The selection of plants as biofilters with high potency to absorb the harmful substances from indoor air within the collection of tropical plants of Gryshko national Botanic Garden has been undertaken. The quantitative and qualitative criteria of both the leaf structure and the photosynthetic apparatus, determining the ability of plants to absorb pollutants, were assessed. Biotechnological methods of plant propagation, involved in phytounits have been worked out. Different types of containers with an automatic watering system and substrata with low part of organic substances have been proposed. Additionally, plant compositions were equipped by leD lamps elaborated to provide plants with optimal full spectrum for photosynthetic performance. The screening of antimicrobial activity of phytounits was undertaken in the departments of the Center for innovative Medical Technologies. it has been established that an air contamination by Staphylococcus saprophyticus after two-week exposition was reduced by half. Conclusions. Thus, phytomodules, including the plants species which are nontoxic, with high remediation ability and tolerant to various abiotic factors have been provided to be introduced into indoor area of treatment and preventive care establishments and closed deployment places of security forces units.